Comparison of the Clinical Recovery after Nerve Defect Reconstruction Using 4 Different Methods – Experimental Model - Andrei MARIN; Anica DRICU; Georgiana Gabriela MARIN; Carmen GIUGLEA (Modern Medicine)
There are several possibilities for repairing a nerve defect. These include nerve grafting, tissues for bridging, biological or synthetic nerve conduits. Such conduits, alone or filled with different tissues or substances, may be the key for a major breakthrough in the modern treatment of nerve defects. The easiest way to research these new methods is by experimental in vivo research on live animals – such as the Wistar rats. The following article aims to compare 4 different types of repairs for nerve defects: the nerve graft, a biologic nerve conduit (rat aorta), rat aorta with platelet rich plasma and rat aorta with stem cells.